The private sector speaks: investing in sustainable forest management - Chipeta, M.E.; Joshi, M. (Center for International Forestry Research, 2001)
Worldwide, the private sector is expected to play a lead role in economic and production activities, while the public sector provides the supportive policy as well as the legal and other institutional environment for this. National governments of most developing countries have limited financial resources to fund sustainable forest management (SFM) and society is incresingly expecting the rpivate sector to fund SFM. However, the participation of the private sector is not forthcoming as many would like to see. This book presents the papers prepared for the Oslo workshop which convey the perceptions and views of the private sector, including: a glimpse of the currents status of private sector involvement in the forest sector in general, and SFM in particular; the main obstacles the private sector currently faces that deter it from making greater investments; the desired changes in the policy and operating environment which can make conditions more 'enabling for private sector engagement. The first chapter gives a brief background on financing SFM, and a synthesis blending ideas from the papers and the discussions at the workshop on the role of the private sector. The nine chapters are the original Oslo workshop papers.